EXPLOSIVE ORIGIN OF ORE-BEARING CATACLASITES IN THE ALBITITE-URANIUM DEPOSITS OF THE CENTRAL UKRAINIAN SHIELD - Tarasov N.N. (My University, 2004)
Extensional cataclasites in the albitite-uranium deposits of the Ukrainian Shield are spatially and genetically related to sodium metasomatism. They formed within the long-lived Middle Proterozoic fault zones owing to fluid explosions in the ascending flows of deep-seated, alkaline U-bearing solutions. The deformations and spatial distribution of the orebearing cataclasites are defined by multiple fluid explosions in the tectonic zones during alkaline metasomatism and ore deposition.